2022
DOI: 10.1242/bio.059599
|View full text |Cite
|
Sign up to set email alerts
|

shox2 is required for vestibular statoacoustic neuron development

Abstract: Homeobox genes act at the top of genetic hierarchies to regulate cell specification and differentiation during embryonic development. We identified the short stature homeobox domain 2 (shox2) transcription factor that is required for vestibular neuron development. shox2 transcripts are initially localized to the otic placode of the developing inner ear where neurosensory progenitors reside. To study shox2 function, we generated CRISPR-mediated mutant shox2 fish. Mutant embryos display behaviors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…HOX family genes are key factors regulating early hindbrain development and segmentation (Frohman et al, 1990; McNulty et al, 2005). SHOX2 is required for vestibular statoacoustic neuronal development with nerve fibres mostly terminating in the pons and medulla oblongata (hindbrain regions) (Laureano et al, 2022). Immunofluorescence staining of HOXA5 and SHOX2 markers demonstrated that the fluorescence intensity of SHOX2 and HOXA5 decreased following T. pallidum infection, thereby revealing that T. pallidum inhibited the development and maturation of hindbrain neurons on organoids, which was again confirmed by the scRNA-seq analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…HOX family genes are key factors regulating early hindbrain development and segmentation (Frohman et al, 1990; McNulty et al, 2005). SHOX2 is required for vestibular statoacoustic neuronal development with nerve fibres mostly terminating in the pons and medulla oblongata (hindbrain regions) (Laureano et al, 2022). Immunofluorescence staining of HOXA5 and SHOX2 markers demonstrated that the fluorescence intensity of SHOX2 and HOXA5 decreased following T. pallidum infection, thereby revealing that T. pallidum inhibited the development and maturation of hindbrain neurons on organoids, which was again confirmed by the scRNA-seq analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior compartment innervates the utricle, the anterior and lateral cristae, and the posterior compartment innervates the saccule and posterior cristae ( Figure 1C ) ( Sapède and Pujades, 2010 ; Taberner et al, 2017 ). Interruption of various early-expressing differentiation genes, such as Hh ( Sapède and Pujades, 2010 ) and short stature homeobox domain 2 ( shox2 ) ( Laureano et al, 2022 ), reduced and disorganized the SAG, and in the case of Hh, induced fibers from the compartments to extend to the wrong epithelium. Sapède and Pujades, 2010 traced SAG innervation in zebrafish embryos prior to when the lagena is developed, but given its locations in the pars inferior it is likely that the lagena too is innervated by the posterior SAG compartment.…”
Section: Introductionmentioning
confidence: 99%